Optimization of the Old Design of Double Axle Truck Tailgate Arm and Comparison of Loading Simulation of the New Double Axle Truck Tailgate Arm Design Using FEM (Altair Inspire) - Hengki Frisa Sukresno; Erwin; Dedy Triawan Suprayogi (Fakultas Teknik Universitas Pancasila, 2026)
This study optimizes and compares the structural performance of Type A and Type B tailgate frame arm designs for double commercial trucks to improve safety, efficiency, and regulatory compliance. Analytical calculations and Finite Element Analysis using Altair Inspire were employed under a 650 kg operational load. Three materials ASTM A36, Aluminium 7075-T6, and Stainless Steel AISI 304 were evaluated in terms of stress, displacement, and safety factor. Results indicate that the Type B design reduces displacement by approximately 40% compared to Type A, while improving load distribution and structural stiffness. Aluminium 7075-T6 provides the best strength to weight ratio, whereas ASTM A36 remains the most cost-effective option. Only the Type B design complies with the Indonesian Ministry of Transportation clearance requirement (<200 mm). These findings demonstrate that Altair Inspire supports an effective optimization workflow for developing lighter, safer, and regulation compliant tailgate frame arm designs.